Effects of whole-body MRI on outpatient health service costs: a general-population prospective cohort study in Mecklenburg-Vorpommern, Germany - Henry Völzke; Katrin Hegenscheid; Jean-Francois Chenot; Carsten Oliver Schmidt; Elizabeth Sierocinski; Sebastian-Edgar Baumeister (BMJ Open, 2022)
Objective Whole-body MRI (wb-MRI) is increasingly used in research and screening but little is known about the effects of incidental findings (IFs) on health service utilisation and costs. Such effects are particularly critical in an observational study. Our principal research question was therefore how participation in a wb-MRI examination with its resemblance to a population-based health screening is associated with outpatient service costs.Design Prospective cohort study.Setting General population Mecklenburg-Vorpommern, Germany.Participants Analyses included 5019 participants of the Study of Health in Pomerania with statutory health insurance data. 2969 took part in a wb-MRI examination in addition to a clinical examination programme that was administered to all participants. MRI non-participants served as a quasi-experimental control group with propensity score weighting to account for baseline differences.Primary and secondary outcome measures Outpatient costs (total healthcare usage, primary care, specialist care, laboratory tests, imaging) during 24 months after the examination were retrieved from claims data. Two-part models were used to compute treatment effects.Results In total, 1366 potentially relevant IFs were disclosed to 948 MRI participants (32% of all participants); most concerned masses and lesions (769 participants, 81%). Costs for outpatient care during the 2-year observation period amounted to an average of €2547 (95% CI 2424 to 2671) for MRI non-participants and to €2839 (95% CI 2741 to 2936) for MRI participants, indicating an increase of €295 (95% CI 134 to 456) per participant which corresponds to 11.6% (95% CI 5.2% to 17.9%). The cost increase was sustained rather than being a short-term spike. Imaging and specialist care related costs were the main contributors to the increase in costs.Conclusions Communicated findings from population-based wb-MRI substantially impacted health service utilisation and costs. This introduced bias into the natural course of healthcare utilisation and should be taken care for in any longitudinal analyses.